Total-body PET - Poje, Urška (Matrika, 2019)
PET is widely considered the most sensitive technique avaliable for noninvasive studying physiology, metabolism, and molecular path-ways in the living human being. However, PET remains constraint by factors including low signalto-noise ratio, long imaging times, and concerns about radiation dose. By increasing the geometric coverage to cover the entire body, sensitivity can be increased by factor of about 40 fot total-body or a factor of about 4-5 for imaging a single organ. World's first total-body PET/CT scanner is currently under construction.
Keywords: medical imaging; medical physics; medicinska fizika; medicinsko slikanje; positron emission tomography; pozitronska emisijska tomografija